The Matrix Model of the Tactical Prospects of the Company’s Sales Logistics - Kuznetsova, Anastasia A.; Novosadov, Sergey A.; Kobylina, Elena V.; Repetskaya, Natalia V. (The journal of contemporary issues in business and government, 2021)
An enterprise constantly needs to improve its sales logistics. The purpose of the work is to create a matrix of tactical prospects for the company’s sales logistics. Tasks for conducting a comprehensive study of the scientific and methodological support of ABC analysis methods have been identified; the use of the economic and mathematical apparatus for modeling the sales matrix; a description of the methodology for building the sales matrix and identifying the tactical prospects of the enterprise. The study relies on systemic and process approaches. The main methods are methods of statistical, economic, and mathematical analysis. The presented matrix model is based on the creation of individual contract sales conditions, grounding on multi-parameter ratings of customers and goods. It is shown that the regulation of relations and flows in the sales sector can be carried out on the basis of standard decisions taken from the proposed model of the matrix of sales logistics.